Increasing Fracture Toughness and Transmittance of Transparent Ceramics using Functional Low-Thermal Expansion Coatings. Issue 1 (December 2018) - Merac, Marc; Bram, Martin; Malzbender, Jürgen; Ziegner, Mirko; Rasinski, Marcin; Guillon, Olivier
Abstract Transparent polycrystalline ceramics have the potential to enable applications no other materials can, but to do so their strength and toughness must be improved. However, surface strengthening treatments like those used for glasses have so far remained elusive. Here for the first time, we report on engineering unprecedented surface compression, of the magnitude achieved for ion-exchange strengthened glasses (~750 MPa) in transparent ceramics. This was achieved by applying functional, low thermal-expansion yttria coatings onto yttria-stabilized zirconia substrates and thermally treating. In some instances, the treatment more than doubled the fracture toughness while simultaneously increasing light transmittance.